Coleorhiza‐enforced seed dormancy: a novel mechanism to control germination in grasses. Issue 4 (16th October 2020) - Holloway, Thomas; Steinbrecher, Tina; Pérez, Marta; Seville, Anne; Stock, David; Nakabayashi, Kazumi; Leubner‐Metzger, Gerhard
Summary: How the biophysical properties of overlaying tissues control growth, such as the embryonic root (radicle) during seed germination, is a fundamental question. In eudicot seeds the endosperm surrounding the radicle confers coat dormancy and controls germination responses through modulation of its cell wall mechanical properties. Far less is known for grass caryopses that differ in tissue morphology. Here we report that the coleorhiza, a sheath‐like organ that surrounds the radicle in grass embryos, performs the same role in the grass weed Avena fatua (common wild oat). We combined innovative biomechanical techniques, tissue ablation, microscopy, tissue‐specific gene and enzyme activity expression with the analysis of hormones and oligosaccharides. The combined experimental work demonstrates that in grass caryopses the coleorhiza indeed controls germination for which we provide direct biomechanical evidence. We show that the coleorhiza becomes reinforced during dormancy maintenance and weakened during germination. Xyloglucan endotransglycosylases/hydrolases may have a role in coleorhiza reinforcement through cell wall remodelling to confer coat dormancy. The control of germination by coleorhiza‐enforced dormancy in grasses is an example of the convergent evolution of mechanical restraint by overlaying tissues.